2022
DOI: 10.1002/jhet.4562
|View full text |Cite
|
Sign up to set email alerts
|

Methoxy‐activated indole‐7‐carbohydrazides; synthesis, antioxidant, and anticancer properties

Abstract: Indole has been known as a key heterocyclic motif in the development of new structures for both chemical and biological properties. In this current study, a new range of indole-7-carbohydrazides has been successfully synthesized starting from the readily available 3-phenyl and 2,3-diphenyl 4,6-dimethoxyindoles.The structures of the novel compounds were confirmed by utilizing 1 H NMR, 13 C NMR, FT-IR, high-resolution mass spectrometry, and single crystal X-ray diffraction techniques. In addition, the indole-7-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Therefore, the experiment was repeated by in a mixture of THF and methanol and it was determined that the starting material was exhausted after 24 hours. After the reaction, it was also determined that the indole-7-hydrazonomethyl 6 is highly reactive and has rapid degradation potential and therefore it was used for the next reaction shortly after its synthesis [35]. In the last step, compound 6 was spun in acetone at room temperature and the targeted indole 7 was successfully synthesized (figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the experiment was repeated by in a mixture of THF and methanol and it was determined that the starting material was exhausted after 24 hours. After the reaction, it was also determined that the indole-7-hydrazonomethyl 6 is highly reactive and has rapid degradation potential and therefore it was used for the next reaction shortly after its synthesis [35]. In the last step, compound 6 was spun in acetone at room temperature and the targeted indole 7 was successfully synthesized (figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Isatin‐carbohydrazide hybrids also possessed promising activity against BC cells, and among them, hybrid 77 (IC 50 : 0.99 µM) was fivefolds more potent than sunitinib (IC 50 : 4.77 µM). [ 118,119 ] Moreover, isatin‐thiosemicarbazone hybrid 78 (IC 50 : 23.42 and 19.68 µM) demonstrated potential activity against MCF‐7 and MDA‐MB‐231 cell lines. [ 120 ]…”
Section: Miscellaneous Indole/isatin Hybridsmentioning
confidence: 99%
“…Hakan Kandemir et al [118] reported a protocol for synthesis of 7-hydrazonomethyl-4,6-dimethoxyindoles 575 (a-b) and 4,6dimethoxyindole based carbohydrazides 576 (a-j). Initially 4,6dimethoxyindoles 573 (a-b) were reacted with POCl 3 and DMF at 0 °C for 6 h to yield indole-7-carbaldehydes 574 (a-b) followed by reaction with hydrazine and ethanol at room temperature yielded corresponding 7-hydrazonomethyl indoles 575 (a-b).…”
Section: (A4)mentioning
confidence: 99%
“…Hakan Kandemir et al [118] . reported a protocol for synthesis of 7‐hydrazonomethyl‐4,6‐dimethoxyindoles 575 (a–b) and 4,6‐dimethoxyindole based carbohydrazides 576 (a–j) .…”
Section: Chemistry Of Indole Based Heterocycle Scaffoldsmentioning
confidence: 99%